PENINGKATAN PROSES PENGOLAHAN KERUPUK IKAN DI DESA BAGAN PETE KECAMATAN ALAMBARAJO KOTA JAMBI - Sukadi S; Novarini N; Hilda Porawati (Politeknik Negeri Sriwijaya, 2020)
One of the craftsmen of fish cracker makers typical in Jambi City is the Tiara Jambee Crackers partner. The obstacle in the partners is the low sales of fried crackers compared to raw crackers (not yet fried) because there is not unbalanced profitability of sales of raw crackers compared to fried crackers. This is because the typical crackers of Jambi City are 2 to 3 times the size of other types of crackers in other regions so that frying requires a large volume of cooking oil. In addition to the problem of frying, marketing is not optimal because the packaging has not been labeled and still uses the method conventional waiting for consumers to come to partners Jambee crackers. The results of processing crackers without using oil have advantages in the texture, shape, and color of crackers so that this can increase cracker sales.